Types and Functions of Teacher Questions on Thematic Learning of Curriculum 2013 at Primary Schools - Meida, Amelia Annis; Zulaeha, Ida; Alimah, Siti (Journal of Primary Education)
Teachers question is a habitual activity for affect students' thinking skills in thematic learning of Curriculum 2013. The activity is believed able to improve the students’ thinking skills. Its levels at primary school, according to Anderson taxonomy, can be grouped into high and low-levels. This research has a purpose of finding out the types and functions of the teachers' question in learning at primary school that impact students’ thinking skills. This qualitative descriptive by using simak method to collect the data and advance technique to observe at school. Based on the observation, the most frequently used type of questions by the teacher at lower grade was a low-level question, such as a question to understand. For teachers in higher grades, the tendency of the type of question remembered the question. Both types of teacher questions provide a low-level impact on students' thinking skills. The function of the most frequently used question was checking to understand. The function of question inside of learning interaction depended on the context, such as background, situation, purpose, topic, and doers. Good question in the specific context of interaction could be a trigger to motivate students in strengthening their reasoning and learning.